An Alternative Approach To Narcotics Trafficking Eradication In Indonesia: Institutional Perspectives From The National Narcotics Agency - Irzan Haryono; Dey Ravena; Dini Dewi Herniati; Nandang Sambas; Efik Yusdiansyah; Chepy Firman Ali Zakaria (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The Prevention and Eradication of Narcotics Abuse and Illicit Trafficking (P4GN) represents Indonesia’s principal national policy response to the escalating narcotics threat. This study evaluates the effectiveness of P4GN implementation by the National Narcotics Agency (BNN) and proposes an alternative model to strengthen its policy framework. Recognizing narcotics abuse as not merely a legal violation but also a complex social and public health issue, the research underscores the need to integrate legal, institutional, and socio-cultural dimensions in both policy design and execution. This study adopts a normative legal approach, supported by qualitative analysis of key regulatory instruments, including Law No. 35 of 2009 on Narcotics, Presidential Instructions, the National Action Plan for P4GN (RAN P4GN), and internal BNN regulations. The analysis focuses on policy coherence, orientation, and implementation gaps within the existing framework. The findings reveal that, despite a relatively comprehensive legal and institutional foundation, P4GN implementation remains predominantly repressive. Current strategies prioritize law enforcement while insufficiently addressing prevention, rehabilitation, and community empowerment. Moreover, the absence of clear differentiation between drug users and traffickers undermines policy effectiveness and raises human rights concerns, ultimately limiting the sustainability of narcotics control efforts. To address these shortcomings, this study proposes an alternative policy model that reconfigures P4GN through a more balanced and integrated approach. The model emphasizes legal reform, institutional strengthening, and transformation of legal culture, while prioritizing preventive measures, rehabilitation, and community engagement alongside targeted enforcement against drug syndicates. It also advocates the use of data-driven strategies and information technology to enhance coordination. Within this framework, BNN is repositioned as a central cross-sectoral coordinator, promoting synergy among stakeholders. Grounded in public health and restorative justice perspectives, the model offers a more adaptive, effective, and humane approach to narcotics control in Indonesia.